2021
DOI: 10.1002/admi.202101528
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Marriage of Catalyst Nanoparticles and Mesoporous Supports

Abstract: The marriage of catalyst nanoparticles and mesoporous supports brings exciting new opportunities in the field of catalysis, which provides the ability to create advanced nanoporous catalysts for a wide range of catalytic processes. It has been found that not only the features of mesoporous supports, such as, surface areas, mesostructures, and pore sizes, are critical for the catalytic performances, but also the unique properties of catalyst nanoparticles, including dispersion, particle size, and loading amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…62 As compared to bulk analogs, metal NPs possess high surface area, good electrical conductivity, abundant active sites, and exclusive electronic structure, leading to superior electrocatalytic activity. 63,64 A wide range of metal NPs has been recently investigated for electrochemical sensing. Especially, gold NPs (AuNPs) displayed exquisite performance for the nonenzymatic detection of lactate.…”
Section: Materials Developed For Nonenzymatic Lactate Sensing Metal N...mentioning
confidence: 99%
“…62 As compared to bulk analogs, metal NPs possess high surface area, good electrical conductivity, abundant active sites, and exclusive electronic structure, leading to superior electrocatalytic activity. 63,64 A wide range of metal NPs has been recently investigated for electrochemical sensing. Especially, gold NPs (AuNPs) displayed exquisite performance for the nonenzymatic detection of lactate.…”
Section: Materials Developed For Nonenzymatic Lactate Sensing Metal N...mentioning
confidence: 99%
“…Mesoporous materials, especially ordered mesoporous materials, have emerged as excellent supports for immobilizing catalytically active metal species in the field of heterogeneous catalysis in recent years. These materials have unique features, such as high surface areas, large pore volumes, narrow and well-defined pore size distribution (PSD), and accessible pores with tunable characteristics (i.e., size, shape, and surface functionality), which altogether enable them to provide a versatile matrix for homogeneous and stable dispersion of metal species inside their nanospaces and thus enhance the activity and stability of the resulting supported catalysts in various applications. , Ordered mesoporous carbons (OMCs) are a promising family of porous materials for application as catalyst supports. In addition to the features mentioned above, these materials have excellent chemical, thermal, and mechanical stability. , However, despite the extensive use of porous carbons as support in diverse and important organic transformations and well-documented electrochemical studies, their utility in the oxidative coupling reaction of alcohols and amines to imines, especially as support for Ru species, is less known and underdeveloped. Therefore, we aimed to investigate the activity of a novel catalyst system consisting of ruthenium species supported on a three-dimensional (3D) cubic OMC (CMK-8) in the aerobic oxidative coupling of alcohols and amines.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have unique features, such as high surface areas, large pore volumes, narrow and well-defined pore size distribution (PSD), and accessible pores with tunable characteristics (i.e., size, shape, and surface functionality), which altogether enable them to provide a versatile matrix for homogeneous and stable dispersion of metal species inside their nanospaces and thus enhance the activity and stability of the resulting supported catalysts in various applications. 34,35 Ordered mesoporous carbons (OMCs) are a promising family of porous materials for application as catalyst supports. In addition to the features mentioned above, these materials have excellent chemical, thermal, and mechanical stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The pores in porous carbon materials are divided into micropores (<2 nm), mesopores (2–50 nm), and macropores (>50 nm) according to their sizes . The catalytic performance of carbon-supported metal catalysts usually depends on carbon supports; in particular, it is closely related to their pore structures including pore size and pore distribution. For instance, Xing et al used a variety of carbon materials with different pore structures as cathode catalysts and revealed that the pore shape had a significant effect on the catalytic performance, and large pores were beneficial to maintain a good reaction interface and promote the reaction . Luo et al reported mesopore structure in carbon support was conducive to the dispersion of active metals and the mass transfer and diffusion in the hydrogenolysis reaction of lignin, thus improving the catalytic performance .…”
Section: Introductionmentioning
confidence: 99%